Plasma alterations in Immunoglobulin G (IgG), Immunoglobulin M (IgM) and immunoglobulin A (IgA) , serum transferrin (TFN), serum albumin (ALB) and prealbumin (PA), Interleukin (IL-6) and serum C-reactive protein (CRP) after immune-type enteral nutrition s: Plasma alterations in Immunoglobulin G (IgG), Immunoglobulin M (IgM) and immunoglobulin A (IgA) , serum transferrin (TFN), serum albumin (ALB) and prealbumin (PA), Interleukin (IL-6) and serum C-reactive protein (CRP) - Cui, Xiaoxu; Wu, Haiping (Journal of Medical Biochemistry, 2025)
Objective: To explore the effects of immune-type enteral nutrition support on postoperative recovery and nutritional status and Plasma alterations in Immunoglobulin G (IgG), Immunoglobulin M (IgM) and immunoglobulin A (IgA) , serum transferrin (TFN), serum albumin (ALB) and prealbumin (PA), Interleukin (IL-6) and serum C-reactive protein (CRP)  of patients undergoing radical resection of colon cancer.Methods: From January 2023 to December 2024, 106 patients with colon cancer who underwent radical resection of colon cancer were selected as the study objects. Patients were divided into control group (CG) and observation group (OG) according to random number table method. The CG received routine nursing intervention plus routine parenteral nutrition support. The OG implemented high-quality nursing intervention based on the CG plus immune-type enteral nutrition support. The postoperative recovery time, nutritional indicators, immune function, inflammatory response, quality of life, incidence of complications along with nursing satisfaction in 2 groups were compared.Results: In comparison with the CG, the the recovery time of bowel sound, time of exhaust gas, time of defecation, time of getting out of bed and hospital stay in the OG presented shorter (P
Keywords: colon cancer, radical resection, high-quality nursing, immune, enteral nutrition, Plasma alterations in Immunoglobulin G (IgG), Immunoglobulin M (IgM) and immunoglobulin A (IgA) , serum transferrin (TFN), serum albumin (ALB) and prealbumin (PA), Interleukin (IL-6) and serum C-reactive protein (CRP)